Single Molecule Magnets of Co2 and Co2La MOFs Synthesized by New Schiff Base Ligand N,N′-bis(o-Vanillinidene) Ethylenediamine (o-VEDH2) - Ghosh, Mithun Kumar; Jana, Barun; Ghorai, Tanmay Kumar (Frontiers in Chemistry, 2020)
Schiff base ligand N,N'-bis(O-vanillinidene) ethylenediamine (o-VEDH2) has been employed to synthesize new [CoIICoIV(o-VED)(OAc)2(μ2-OAc)(OMe)]•MeOH (1) and [Co2IV(o-VED)2(en)2(NCCH3)(OCH3)][La(NO3)6]( NO3-)•2MeOH•MeCN•H2O (2) MOFs those have interesting Single Molecule Magnets (SSMs) property. The synthesized complexes are characterized by Single crystal X-ray diffraction, FT-IR spectroscopy, UV-visible spectroscopy and squid magnetic measurement. Single crystal X-ray data show that both the complexes crystallizes in the monoclinic crystal system with P21/c(14) and P21/n(14) space groups and generate unique MOF like structures. Overall, both the metal centres of 1 form octahedral geometry with a butterfly core structure. Variable-temperature (T) and field (H) solid-state direct-current (dc) and alternative current (ac) magnetic susceptibility measurements were performed on both the complexes over 1.8-300 K, which exhibited a ground state spins (S) of 4 and 5 of complexes 1 and 2, respectively. The AC out-phase and in-phase properties of complexes show SMMs. Other properties like optical, sensing and DNA binding interaction also investigated by the complexes. Complexes 1 and 2 have energy band gaps of 3.7 and 3.03 eV indicates semiconductor properties. Simultaneously, complex 1 was found to sense H2O2 with a rate constant (k) = 1.59 × 10-4 s-1 whereas complex 2 was found to bind with CT-DNA by intercalation mode with binding constant (Kb) of 1.22 × 105 M-1.